Cognitive Component in the Structure of Students’ Legal Consciousness in the Analysis of Economic Offence Cases - Ирина Н. Погожина; Марина В. Сергеева (Rossijskij psihologičeskij žurnal., 2021)
Introduction. The cognitive component in the structure of students’ legal consciousness still remains an understudied area. It is unclear how students use the content of representations of economic offences in the analysis of potentially unlawful situations. This study aims to identify and examine the content of cognitive component elements in the structure of students’ legal consciousness in the process of solving economic offence cases (exemplified by corruption risk situations) – namely, representations of corruption, cognitive skills required to recognize it, and characteristics of the relationship between these elements. Methods. The correlation and regression study involved 119 students of Moscow universities. The diagnosis of variables was performed using authors’ original diagnostic tools (the Open-Ended Questions and the Test of the Ability to Recognize Economic Offences). Results. We observed significant correlations between the content of students’ representations of economic offences exemplified by corruption (‘knowledge’) and the level of the cognitive ability to identify essential characteristics of economic offences (‘characteristics’) (ρ = 0.438; p ≤ 0.01), as well as between the content of students’ representations of economic offences (‘knowledge’) and the cognitive ability to apply the rule of logical inference when recognizing economic offences in corruption risk situations (‘inference’) (ρ = 0.441; p ≤ 0.01). We found a significant impact of the ‘characteristics’ and ‘inference’ variables on the ‘knowledge’ variable (p < 0.05). Discussion. For the first time it has been shown that cognitive component elements of legal consciousness related to representations of economic offences are coordinated with each other. To form complete and generalized representations of economic offences among students, it is necessary to develop their cognitive skills that may enable them to (a) analyze problem situations and identify essential characteristics of economic offences and (b) infer whether the situation can be classified as unlawful. The findings of this study may be used to develop training programs aimed at forming the cognitive component of students’ legal consciousness.